Characterization of Escherichia coli isolates from water and food sold on the streets of Maputo: Molecular typing, virulence genes and antibiotic resistance - Salamandane, Acácio (2022)
The aim of this study was to investigate the pathogenic potential and antibiotic resistance of 59 Escherichia coli isolates from ready-to-eat (RTE) street food (n = 31) and drinking water (n = 28) sold in the city of Maputo, Mozambique. The isolates were characterized by XbaI subtyping analysis via pulsed field gel electrophoresis. Multiplex PCRs were performed targeting five virulence genes (stx, lt, st, astA, and eae) and three groups of antibiotic-resistant genes, namely ß-lactamases (extended-spectrum ß-lactamase and AmpC), tetracycline (tetA, tetB, and tetM) and sulfamethoxazole/ trimethoprim (sul1, sul2, and sul3). The stx virulence gene, encoding the Shiga/Vero (VT) toxin produced by the verotoxin-producing E. coli (VTEC), was identified with similar frequency in isolates from food (5/31) and water (6/28). The highest percentages of resistant isolates from food and water were found for ß-lactams imipenem (35.5 and 39.3%, respectively) and ampicillin (39.3 and 46.4%, respectively). Multidrug resistance was observed in 31.3% of the isolates, being higher in E. coli isolates from water (45.5%) compared to RTE street food isolates (19.2%). Virulence genes were detected in 73% of the multidrug-resistant isolates. Concerning antibiotic-resistant genes, ESBL was the most frequent (57.7%) among -lactamases while tetA was the most frequent (50%) among non- -lactamases